Метод скінченних різниць для еволюційних включень та варіаційних нерівностей - Kasyanov, P. O.; Mel’nik, V. S.; Toscano, L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The method of finite-difference approximations, advanced by C. Bardos and H. Brezis for the nonlinear evolutionary equations, is generalized on differential-operational inclusions which are tightly connected to evolutionary variational inequalities in Banach spaces.